2011
DOI: 10.1149/1.3544941
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Carbon in a Coin-Type Direct Carbon Fuel Cell

Abstract: To date, carbon oxidation in high temperature fuel cells has been classified into two processes: one involves direct oxidation to CO 2 [direct electrochemical process] and the other involves oxidation to CO 2 via a chemical species of CO [chemical-electrochemical (CE) process]. A coin-type direct carbon fuel cell was fabricated on the basis of molten carbonate fuel cell technology. Activated carbon made from bamboo was used as the fuel. Steady state polarization and step chronopotentiometry methods were employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…As the work plan developed, additional experimental set-ups were required, including an elegant experiment developed by Dr. Choong-Gon Lee to demonstrate the role of CO in the anode reaction [11]. Rather than directly dropping carbon into the anode chamber of the DCFC cylinder cell, as typically done, the carbon was contained within a separate alumina fuel cartridge (see Fig.…”
Section: Reverse Boudouard Reaction Cartridge Testmentioning
confidence: 99%
“…As the work plan developed, additional experimental set-ups were required, including an elegant experiment developed by Dr. Choong-Gon Lee to demonstrate the role of CO in the anode reaction [11]. Rather than directly dropping carbon into the anode chamber of the DCFC cylinder cell, as typically done, the carbon was contained within a separate alumina fuel cartridge (see Fig.…”
Section: Reverse Boudouard Reaction Cartridge Testmentioning
confidence: 99%
“…al. 32 reported that the voltage of a MCFC decreased with time to zero in 25 h at a constant current density using bamboo-derived activated carbon as fuel. On the contrary, carbon fuel was still available since the corresponding carbon amount for current generation was much less than that initially loaded.…”
mentioning
confidence: 99%
“…The anode was a porous Ni-Al metal sheet, and the cathode was a porous in situ oxidised NiO. The matrix was made of LiAlO 2 , and the electrolyte was a eutectic mixture of 62 mol% Li 2 CO 3 and 38 mol% K 2 CO 3 [14]. The electrodes and matrices were supplied by the Korean Institute of Science and Technology (KIST).…”
Section: Methodsmentioning
confidence: 99%
“…The SSP measures the correlation between current and voltage from 0 to 150 mA/cm 2 of current density. The SC involved increasing the current from 0 to 150 mA/cm 2 by 50 mA/cm 2 step for 60 s and measuring the voltage relaxations [14], while the EIS measures the impedance by changing the AC signalling of 5 mV RMS from the high frequency (10 kHz) to low frequency (0.01 Hz) at an open-circuit state. All electrochemical ways were carried out after 12 h of cell operation.…”
Section: Methodsmentioning
confidence: 99%